Peru : Trajectories towards Formality - World Bank (Washington, DC, 2013)
This report is the outcome of very close cooperation with the authorities of the Government of Peru. The authorities have been involved in all stages of the process, going back to the first phase of this programmatic study. The authorities proved instrumental in helping design the focus of this report, including the scope of a survey of businesses conducted for this study, the survey questionnaire itself, they also suggested specific topics to be explored, which are presented throughout the report mainly in the form of boxes. This report focuses on the trajectories towards formality of micro and small businesses, drawing insight by polling those businesses directly. The study finds no significant impact of certain characteristics of formality, such as having a municipal license or being registered with the tax authorities, on the profitability of businesses or on their probability of obtaining a loan. These results must be accompanied, however, by the caveat that establishing the impact of informality econometrically is notoriously difficult. The methodology used in this report does not attempt to capture the negative effects that informality may have on the performance of formal firms, or the effects that informality may have in undermining social trust and the overall business environment. The study also finds informality to be particularly persistent in the area of labor relations and access to pension, driven largely by high costs of being formal, limited enforcement of labor relations, and a preference for flexible labor relations. These two findings combined suggest that: (i) efforts to increase the access to health insurance and pension coverage of workers through a shift from informal arrangements to existing formal labor relations will prove difficult; and (ii) alternative methods to increase access to health and pension coverage are well-worth exploring. The rest of these main findings concentrate on the conclusions of the study regarding the determinants of informality and what prompts businesses to move towards formality.